Tingkat Pengetahuan Penderita Tuberculosis Paru Tentang Penularan Penyakit Tuberculosis Paru - Ahmadi (Universitas Nazhatut Thullab Al- Muafa Sampang, 2021)
Introduction: Pulmonary TB is an infectious disease caused by Mycobacterium tuberculosis. The disease is transmitted via droplets with pulmonary tuberculosis in people who are nearby (MOH, 2007). Pulmonary TB patient knowledge about modes of transmission of TB disease Parusangat needed for pulmonary TB in misery is not contagious to others who are nearby. increasingly broad knowledge of a person then it will affect the response positifdalam one's attitude to stimulus associated with pain and prevent transmission of diseases such as pulmonary TB to others. Methods: In this research using descriptive method that aims to present a complete picture of the social setting or for the purpose of exploration and clarification of a phenomenon or social reality, to describe the way a number of variables relating to the issue and studied the phenomenon unit tested. Result: Research shows that most patients with pulmonary TB are knowledgeable enough as many as 22 patients (68.8%) and a small percentage of patients are knowledgeable well as many 1 patient (3.1%). Conclusions: Knowledge influenced by the experience of patients in participating in community activities because of the often follow the activities then the patient will have more time to socialize and interact with people around so that they can gain more knowledge.